PEMANFAATAN QUIZIZZ DALAM MENINGKATKAN KUALITAS BELAJAR MATEMATIKA YANG MENYENANGKAN DI KELAS VII.I SMPN 2 TANJUNG LAGO - Suwiji, Dewi (Universitas Bhinneka PGRI, 2024)
In this digital era, students are more interested in interactive technology such as online games and animation. And this is a challenge for teachers to be able to create an interesting, interactive, and fun learning atmosphere. This research aims to improve the quality and active learning of students in class VII.I SMPN 2 Tanjung Lago using the Quizizz educational application. The aim of this research is: to determine the increase in student learning outcomes in the Value Comparison material for class VII.I at SMPN 2 Tanjung Lago. This type of research is Classroom Action Research (PTK). Data collection using test and observation methods in January 2024. The results of this research are; that there was an increase in average learning outcomes in cycle I by 65% and cycle II by 92%. The disadvantage of Quizizz is that it depends on the internet network. Quizizz can also be used by educators as an alternative ICT-based teaching media (Information and Communication Techniques) to be used as fully as possible in achieving TP.